Effect of lubrication on hardness in the ring compression test. (July 2016) - HariKrishna, CH; Davidson, MJ; Nagaraju, CH; Anil Kumar, B
This paper focuses on the hardness distribution in the AA2014-T6 ring specimens upset under rigid dies. Three different types of lubricants namely soap, boric acid and vaseline were employed as lubricants and the friction factor corresponding to the lubricant employed was evaluated using standard 'Ring compression test'. The strain distributions obtained from the simulation studies were used to predict the hardness inside the ring specimen. The hardness measured experimentally was validated with the predicted hardness and it was found that the errors in the predicted results were less than 10%. The hardness variations inside the upset metallic ring specimens were compared with the deformed solid cylinders to understand the behavior of differential strain hardening. It can be reported from the experimental and predicted results that the hardness is not uniform inside the deformed ring specimen and it varies at the bulge head; on the surface and along the neutral plane.